Yersinia pestis: mechanisms of entry into and resistance to the host cell - Ke, Yuehua; Chen, Zeliang; Yang, Ruifu (Frontiers in Cellular and Infection Microbiology, 2013)
During infection, Yersinia, a facultative intracellular bacterial species, exhibits the ability to first invade host cells and then counteract phagocytosis by the host cells. During these two distinct stages, invasion or antiphagocytic factors assist bacteria in manipulating host cells to accomplish each of these functions; however, the mechanism through which Yersinia regulates these functions during each step remains unclear. Here, we discuss those factors that seem to function reversely and give some hypothesis about how bacteria switch between the two distinct status.